2018
DOI: 10.1002/mnfr.201700730
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Efficacy of Brown Seaweed Lessonia nigrescens Extract on the Gene Expression Profile and Intestinal Microflora in Type 2 Diabetic Mice

Abstract: The above findings suggest that LNE could be considered as a functional food for reducing blood glucose and regulating intestinal microflora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…Furthermore, it also increased the abundances of Lachnospiraceae NK4A136 group and Alisties , affecting the release of intestinal hormones for regulating insulin release. The antidiabetic activity of brown seaweed Lessonia nigrescens ethanolic extract (LNE), including phenolics and flavonoids, was investigated in type 2 diabetic mice fed with a high‐sucrose/high‐fat diet by (Zhao et al., 2018). They showed that the intake of LNE increased the growth of Barnesiella , Helicobacter , and Turicibacter , which were able to stimulate the host's antidiabetic effect, accompanied with the modification in the gene and protein expression of hepatic phosphatidylinositol 3‐kinase and c‐Jun N‐terminal kinase.…”
Section: Dietary Polyphenols and The Gut Microbiome For Diabetesmentioning
confidence: 99%
“…Furthermore, it also increased the abundances of Lachnospiraceae NK4A136 group and Alisties , affecting the release of intestinal hormones for regulating insulin release. The antidiabetic activity of brown seaweed Lessonia nigrescens ethanolic extract (LNE), including phenolics and flavonoids, was investigated in type 2 diabetic mice fed with a high‐sucrose/high‐fat diet by (Zhao et al., 2018). They showed that the intake of LNE increased the growth of Barnesiella , Helicobacter , and Turicibacter , which were able to stimulate the host's antidiabetic effect, accompanied with the modification in the gene and protein expression of hepatic phosphatidylinositol 3‐kinase and c‐Jun N‐terminal kinase.…”
Section: Dietary Polyphenols and The Gut Microbiome For Diabetesmentioning
confidence: 99%
“…The in vivo anti-diabetic efficacy of seaweed has been shown in many animal studies (Gabbia et al 2017;Roy et al 2011;Song et al 2018;Zhao et al 2018). In human clinical trials, daily supplementation with Undaria pinnatifida and Sacchariza polyschides (as Gigantea bulbosa) balances blood glucose levels, decreases serum triglyceride concentrations, and increases high-density lipoprotein cholesterol in subjects with type 2 diabetes (Kim et al 2008).…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…In the same study, these investigators also showed green macroalgae significantly increased the relative abundance of Akkermansia and decreased the proportion of Alistipes and Turicibacter. Zhao et al (2018) reported the anti-diabetic activity of Lessonia nigrescens ethanolic extract. Specifically, Lessonia nigrescens ethanolic extract could selectively enrich the amounts of beneficial bacteria, Barnesiella, as well as reduce the abundances of Clostridium and Alistipes.…”
Section: Phytochemicalsmentioning
confidence: 99%